2017
DOI: 10.1039/c7dt00983f
|View full text |Cite
|
Sign up to set email alerts
|

Rapid self-healing and anion selectivity in metallosupramolecular gels assisted by fluorine–fluorine interactions

Abstract: Metal complexes from perfluoroalkylamide terpyridine self-assemble into anion selective gels, which manifest self-healing and thermal rearrangement in aqueous dimethyl sulfoxide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 85 publications
0
25
0
Order By: Relevance
“…Metallogels exhibit unique mechanical properties in rheological experiments such as self-healing and thixotropy. 6,50 The mechanical properties of DMSO and DMF gels of complex 1 were studied using dynamic oscillatory rheological measurements on the 1.0% gels. In all experiments, premade gels were used to study the rheological properties.…”
Section: Rheological Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Metallogels exhibit unique mechanical properties in rheological experiments such as self-healing and thixotropy. 6,50 The mechanical properties of DMSO and DMF gels of complex 1 were studied using dynamic oscillatory rheological measurements on the 1.0% gels. In all experiments, premade gels were used to study the rheological properties.…”
Section: Rheological Propertiesmentioning
confidence: 99%
“…Recently, it has been shown that perfluoroalkyl substituted 4-aminophenyl-2,2 0 ,6,2 0 -terpyridine can act as a metallosupramolecular gelator resulting in rapid self-healing and anion selectivity. 50 The FÁ Á ÁF interactions have been shown to affect the rheological and mechanical properties of the metallogels. In this work, we show that Pt(II) complexes of alkyl and fluoroalkyl containing terpyridine derivatives undergo a synergistic PtÁ Á ÁPt and FÁ Á ÁF interaction-driven self-assembly leading to rapid gelation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, terpyridine ligands containing perfluoroalkyl chains have been reported to exhibit anion selective gelation and rapid self-healing properties. [25] The transition metal containing gels such as palladium have also been shown to improve the catalytic activities. [26] Metallogels containing Ag(I) as metal ions and pyridine derivatives as ligands, represent one of the extensively studied systems.…”
Section: Introductionmentioning
confidence: 99%
“…Metallo-supramolecular hydrogels are gels in which the back bones are crosslinked by metal-ligand coordination. Generally, the introduction of metal ions into polymer networks usually brings a series of new physical and chemical characteristics to the gels such as photoelectric, catalytic and magnetic properties [21,22,23,24]. Liuyan Tang et al obtained metallo-supramolecular hydrogels, based on amphiphilic polymers, with multi-stimuli responsive properties such as pH, competing ligands and reversible redox gel-sol transition with Fe 2+ [25].…”
Section: Introductionmentioning
confidence: 99%